Wettability and thermal analysis of hydrophobic poly(methyl methacrylate)/silica nanocomposites - Diana Rymuszka; Konrad Terpiłowski; Dariusz Sternik; Marta Tomczyńska-Mleko; Olena Goncharuk (Adsorption Science & Technology)
Hydrophobic poly(methyl methacrylate)/silica layers on the glass support activated with plasma were obtained. Wettability was investigated from the contact angle measurements and surface free energy estimation by means of using contact angle hysteresis approach. The thermal analysis of poly(methyl methacrylate)/silica films was conducted on a STA 449 Jupiter F1, Netzsch in temperature range of 30–950℃. It was found that the thermal stability of the poly(methyl methacrylate)/silica films decreases with increasing poly(methyl methacrylate) amount in the sample. Morphology of the obtained nanocomposites was investigated by means of scanning electron microscopy. The addition of silanized silica to the poly(methyl methacrylate) solution leads to obtaining the film with more hydrophobic properties, the contact angle value over 90°, and the apparent surface free energy lower than 30 mJ/m 2 . The most hydrophobic film was obtained in the case of silica with Θ = 0.63 (Θ – surface fraction coverage with trimethylsilyl groups). Silica particles were well dispersed in the polymer solution which was confirmed by the scanning electron microscopy analysis.